Choose Your Customer - Byrnes, Jonathan; Wass, John (McGraw Hill-Ascent Audio, 2021)
Every year, managers at companies large and small are finding it harder to compete with the likes of Google and Amazon, who are stealing their customers and cornering every conceivable market and service. There is, however, a way for companies to survive-and win-in this era of digital behemoths. Choose Your Customer is a powerful, customer-targeted guide that can help managers level the playing field against their biggest competitors. Written by Jonathan Byrnes, the legendary MIT-based expert on profits, pricing, and strategy, and John Wass, a key member of the team that made Staples a major national brand, Choose Your Customer shows you how to: identify the customers who are the most profitable-and focus on them; provide services and experiences that can't be replicated by the tech giants, no matter how much data they have or how much automation they use; support your chosen customers' diverse and rapidly evolving needs to accelerate profitability and growth; and focus on your real profit core and build dominance in your specific target market. From unbeatable customer service to superior pricing and product selection, Choose Your Customer provides detailed and actionable advice on how to compete successfully with the aggressive giants, grow your customer base, and increase your profits for lasting success.
Online resource; Title from title page (viewed August 17, 2021)
Keywords: Audiobooks; Livres audio